2021
DOI: 10.1177/00034894211026482
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical School Geography and Ranking Influence Residency Match in Otolaryngology?

Abstract: Objective: To elucidate the associations between geographic locations, rankings, and size/funding of medical schools and residency programs among the current otolaryngology residents. Methods: This retrospective cross-sectional study queried otolaryngology residency program websites for relevant publicly accessible information. Location was categorized as Midwest, Northeast, South, and West. Ranking was according to Doximity (residency) and US News and World Report (medical school). Medical school and residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…More than half of residents matched in the same region as their medical school. This finding mirrors the finding by Goshtasbi et al 10 in 2021 in which they report 55% of applicants in otolaryngology match in the same region as their home medical school. Another study by Cox et al 11 in orthopedic surgery found the regional matching rate to be 47% relative to medical school region, 40% relative to undergraduate school region, and 40% relative to hometown region.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More than half of residents matched in the same region as their medical school. This finding mirrors the finding by Goshtasbi et al 10 in 2021 in which they report 55% of applicants in otolaryngology match in the same region as their home medical school. Another study by Cox et al 11 in orthopedic surgery found the regional matching rate to be 47% relative to medical school region, 40% relative to undergraduate school region, and 40% relative to hometown region.…”
Section: Discussionsupporting
confidence: 88%
“…Silvestre et al 12 experienced similar findings at a rate of 49% in plastic surgery residents. A subgroup analysis by Goshtasbi et al 10 shows that this proportion is significantly greater if the medical school is considered a top 25 program. While we were not able to assess medical school competitiveness, the relatively small community of neurosurgeons may make professional or clinical connections meaningful for the application process, which is reflected in other surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medical school location has a stronger association with residency location than undergraduate or home town location 15 . The regional associations were more prominent for students from a top‐25‐ranked, large, or private medical school 16 …”
Section: Discussionmentioning
confidence: 96%
“…15 The regional associations were more prominent for students from a top-25-ranked, large, or private medical school. 16 Despite the association with residency matching, the U.S. News & World Report ranking of the medical school that a physician attended is not associated with patient mortality or readmission rates. 17 This raises the question of why residents at higher-tier otolaryngology programs are more often from higher-ranked medical schools.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide review of NRMP (National Resident Matching Program) data for US allopathic seniors from 2011-2015 found that 63% matched to programs within the same region as their medical school [4]. This "home field" preference has been reported for plastic surgery, otolaryngology, orthopedic surgery, and general surgery [7][8][9][10][11][12]. A similar impact of geographic preferences on program rank-list choices has been reported [13].…”
Section: Introductionmentioning
confidence: 67%